1999
DOI: 10.1007/s002109900084
|View full text |Cite
|
Sign up to set email alerts
|

HMR 1883, a cardioselective KATP channel blocker, inhibits ischaemia- and reperfusion-induced ventricular fibrillation in rats

Abstract: Ventricular fibrillation (VF) is a major cause of sudden cardiac death in which myocardial ischemia plays a leading role. During ischaemia activation of ATP-sensitive potassium channels (K(ATP)) occurs, leading to potassium efflux from cardiomyocytes and shortening of the action potential favoring the genesis of ventricular fibrillation. In confirmation of this concept the sulfonylurea glibenclamide, which stimulates insulin release by inhibition of pancreatic K(ATP) channels, has been shown to inhibit VF in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 26 publications
2
19
1
Order By: Relevance
“…In contrast to the present results, prior studies in pigs [13], dogs [33,42], rats [43] and rabbits [44] have shown a reduction in ischaemic ventricular fibrillation with the sarcolemmal K ATP blocker HMR 1098 or its congener HMR 1883. The effects of K ATP blockade on ischaemic arrhythmias may depend upon the specific conditions of each experimental model [2].…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to the present results, prior studies in pigs [13], dogs [33,42], rats [43] and rabbits [44] have shown a reduction in ischaemic ventricular fibrillation with the sarcolemmal K ATP blocker HMR 1098 or its congener HMR 1883. The effects of K ATP blockade on ischaemic arrhythmias may depend upon the specific conditions of each experimental model [2].…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, sarcK ATP channel blockers ought to be effective in ischemic arrhythmias, by preventing the action potential shortening. This concept is supported by the facts that the selective sarcK ATP channel blocker HMR 1883 effectively prevented ischemia-induced ventricular fibrillation (Billman et al, 1998;Wirth et al, 1999). Blockade of sarcK ATP channels may predispose to aggravate ischemic injury by increasing the Ca 2ϩ influx.…”
Section: Discussionmentioning
confidence: 98%
“…In this regard, inhibition of sarcK ATP channel may prevent the ischemia-induced shortening of refractory period. In fact, the selective sarcK ATP channel blocker HMR 1883 has been shown to prevent ischemia-induced ventricular fibrillation (Billman et al, 1998;Wirth et al, 1999). On the other hand, inhibition of mitoK ATP channels may produce significant damage to the ischemic myocardium.…”
mentioning
confidence: 99%
“…A newly synthesized sulfonylthiourea, HMR1883, and its sodium salt HMR1098, have selectivity to cardiac sarcolemmal K ATP channels against cardiac mitochondrial, pancreatic b-cell, or vascular smooth muscle K ATP channels (8 -11). The potent antiarrhythmic activity of these compounds has been demonstrated in several animal models of acute myocardial ischemia such as anesthetized rats and pigs (12,13), and post-infarcted conscious dogs (7). In order to investigate whether cardioselective K ATP channel block exerts an antiarrhythmic effect in an old myocardial infarction model, we examined effects of intravenous HMR1098 on the ventricular arrhythmias induced by programmed electrical stimulation (PES) in comparison with a nonselective K ATP channels blocker, glibenclamide.…”
Section: Atp-sensitive Kmentioning
confidence: 99%
“…Glibenclamide: The effects of glibenclamide on arrhythmias have been investigated in models of acute myocardial ischemia in dogs (7) and acute ischemiareperfusion in rats (12). Those studies showed that this drug is antiarrhythmic at a dose of 1 mg / kg (i.v.).…”
Section: Induction Of Arrhythmias By Pesmentioning
confidence: 99%